Editorial Volume 6 Issue 5 - Ron Perrin; Greg Laing; Ciorstan Smark (Australasian Accounting, Business and Finance Journal, 2012)
The articles published in this issue of AABFJ cover a variety of discipline areas as well as providing a contrast in methodologies for research. Cheung and Powell (2012) provide guidance on the use of the Excel modelling package to construct parametric and Monte Carlo Simulation models. Lama (2012) examined the relationship between corporate governance and a firm’s performance as measured by return on equity, earning yield and return on assets, and found and found that in mid-sized Australian ASX companies there was a positive correlation. Morunga and Bradbury (2012) report on the data overload found in the financial reports of New Zealand companies as a result of the disclosure requirements emanating from the adoption and implementation of the International Financial Reporting Standards in New Zealand.
Keywords: Editorial